Recent ecological change in a remote Scottish mountain loch: An evaluation of a Cladocera-based temperature transfer-function - Kattel, GR; Battarbee, RW; Mackay, AW; Birks, HJB (ELSEVIER SCIENCE BV, 2008)
Recent ecological changes in a small Scottish mountain loch, Loch Coire Fionnaraich (LCFR), were inferred using Cladocera analysis and an application of a Cladocera-based temperature transfer-function approach. Modem assemblages of Cladocera from 68 mountain lakes in Scotland and Norway were used to derive the transfer function. Among 21 measured environmental variables, mean summer lake surface-water temperature (LSWT) accounted for the highest (8%) variation in a redundancy analysis of the modem data. A quantitative inference model (r(2) = 0.72, RMSEP = 1.81 degrees C) for summer LSWT was developed using linear partial least squares regression and calibration. The resulting reconstructed summer LSWT at LCFR was compared with local instrumental air-temperature records over the last 20 yr and the Central England Temperature (CET) series over the last 110 yr. The reconstruction showed a broadly similar pattern to the local instrumental temperature records. However, the relationship between the longer CET series and reconstructed summer LSWT was poor suggesting that the site was relatively insensitive to temperature changes prior to the recent warming of the last few decades. Clear changes in Cladoceran species diversity and relative abundance of littoral taxa coincident with the most recent period of climate warming recorded both locally and in the CET suggest that Cladocera do respond to climate change. However, their response to temperature is complex and indirect. The underlying mechanism leading to change in Cladocera assemblages may involve changes in trophic status and habitat availability of the system. It is concluded that understanding other factors such as atmospheric pollution, controls of community dynamics of Cladocera and the overall ecological complexity of mountain lakes is required before any reliance can be placed on a Cladocera-temperature transfer-function for reconstructing climatic change. Crown Copyright (c) 2008 Published by Elsevier B.V. All rights reserved.